Patient willingness to undergo efavirenz dose reduction based on pharmacogenetic testing. (May 2016) - Mitchell, Margaret; Wells, Caroline; Zhang, Xuechao; Hughes, Joshua; White, Je'Purde; Nash, Robertson; Haas, David W
Aim: Among HIV-infected adults receiving efavirenz fixed-dose combination tablets, genotyping could guide efavirenz dose reduction but would require more pills.Methods: We assessed willingness to dose reduce among 129 patients at an HIV primary care clinic in the southeastern USA.Results: When told that switching from one pill to two or three pills "might make you feel a little better", 47% expressed definite or possible willingness. This decreased to 9% if there was "a small chance it might not control your HIV as well". Clinical variables were not associated with willingness.Conclusion: Many patients receiving a fixed-dose combination tablet may be willing to take more pills in order to dose reduce, guided by genetic testing, but only if virologic control is not compromised.